F64 Suicidal ideation and sleep disturbances by disease stage: evidence from the Huntington's disease burden of illness (HDBOI) study for europe (EU5). (12th September 2022) - Rodriguez-Santana, Idaira; Willock, Rosa; Frank, Samuel; Mestre, Tiago; Arnesen, Astri; Hamilton, Jamie L; Hubberstey, Hayley; Winkelmann, Michaela; Hernandez-Jimenez, Elena; Dolmetsch, Ricardo; Ratsch, Sarah; Ali, Talaha M
Abstract : Background: Sleep disturbances and an increased risk of suicide are common in people with Huntington's disease (PwHD), with rates significantly higher than those of the general population as well as other neurodegenerative diseases. However, the magnitude of these problems is still poorly understood. In this piece, we provide evidence for five European countries (EU5) using data from Huntington's Disease Burden of Illness (HDBOI) study. Methods: The HDBOI is a retrospective, cross-sectional study in which physicians reported information on PwHD demographic and clinical characteristics, including suicidal ideation. Moreover, PwHD completed the HDQLife tool including information on concerns about death and dying as well as sleep disturbances through an optional questionaire. PwHD were classifed as early (ES), mid (MS) or advanced stage (AS), according to the opinion of the treating physician. Results: The sample had 1, 602 PwHD ( Table 1 ) of which were 40% ES, 34% MS, and 26% AS. Suicidal risk increased for more advance stages: 12% of ES, 12% of MS and 14% of AS were currently displaying suicide ideation. Overall, over 5% of PwHD had attempt suicide. HDQLife results showed that 61% PwHD felt anxiety about dying and 12% presented suicidal thoughts often or always. Over 46% of PwHD (N=445) reported to have moderate or severe difficulty sleeping and the percentage increases up to 70% for AS. Conclusion: Sleep disturbances and suicidal ideation are high among PwHD and increase as diseases progresses. Interventions aimed at ensuring the provision of adequate mental health and preventive services for PwHD are required to reduce the burden on PwHD.